Analysis and Full-Scale Testing of New MASH TL-4 Bridge Rail for William P. Lane, JR. Bridge, Annapolis, MD. Issue 2 (February 2023) - Williams, William; Lopez, Maria; Eshenaur, Scott; Hopper, Travis
The purpose of this project was to analyze and test a new combination concrete and metal bridge rail for the William P. Lane (WPL) Bridge over the Chesapeake Bay east of Annapolis, Maryland, U.S., to Manual for Assessing Safety Hardware (MASH) Test Level 4 (TL-4) specifications. The new combination bridge rail is 50 in. in height and anchors to an 8 in. thick segmental precast concrete deck. The bridge rail was anchored to the deck using widely spaced 1 in. diameter bent anchor bolts that were cast into the concrete parapet sections. The length of the parapet and deck sections were approximately 150 ft. The deck sections were constructed with tongue and groove joint connections. The single tube metal rail, which bolted to the top of the concrete parapet sections, was anchored to the concrete using conventional cast in place anchor bolts. The transverse reinforcement in the deck, in the immediate area of the MASH TL-4 impact, was instrumented with strain gages to measure the strain and force in the transverse deck reinforcement. In addition, load cells were applied to the 1 in. diameter anchor bolts in the parapet to measure the anchor forces from the MASH TL-4 impact. This paper summarizes the results from the bridge rail analyses, measured forces in the transverse deck reinforcement and anchor bolts from the crash loads, and the results from the full-scale testing program. The new combination bridge rail performed very well with respect to the MASH TL-4 specifications. Details of the design and testing of the combination bridge rail are provided in this paper.